Structural and functional stabilization of protein entities: state-of-the-art - Balcão, V. M. (2015)
Within the context of biomedicine and pharmaceutical sciences, the issue of (therapeutic) protein stabilization assumes particular relevance. Stabilization of protein and protein-like molecules translates into preservation of both structure and functionality during storage and/or targeting, and such stabilization is mostly attained through establishment of a thermodynamic equilibrium with the (micro)environment. The basic thermodynamic principles that govern protein structural transitions and the interactions of the protein molecule with its (micro)environment are, therefore, tackled in a systematic fashion. Highlights are given to the major classes of (bio)therapeutic molecules, viz. enzymes, recombinant proteins, (macro)peptides, (monoclonal) antibodies and bacteriophages. Modification of the microenvironment of the biomolecule via multipoint covalent attachment onto a solid surface followed by hydrophilic polymer co-immobilization, or physical containment within nanocarriers, are some of the (latest) strategies discussed aiming at full structural and functional stabilization of said biomolecules.